2016
DOI: 10.1039/c6nj00808a
|View full text |Cite
|
Sign up to set email alerts
|

A recyclable Mn–porphyrin catalyst for enantioselective epoxidation of unfunctionalized olefins using molecular dioxygen

Abstract: A highly efficient green process for the asymmetric epoxidation of olefins by an easy to synthesise Mn–porphyrin and O2/aldehyde is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 81 publications
0
33
0
Order By: Relevance
“…[16,[19][20][21][22][23][24][25] Nowadays, magnetite nanoparticles are of particular interest because of their unique properties including high surface area, low toxicity, ability to be separated and biocompatibility. [16,[26][27][28][29][30] Magnetic separation renders the recycling of catalysts from solution using external magnetic fields much easier than filtration and centrifugation. In continuation of our previous investigation of catalytic activity of Schiff base complexes, [6,[9][10][11]15,19] herein we report the anchoring of novel cisdioxomolybdenum(VI) macrocyclic Schiff base complex by reaction of 1,4-bis(2-carboxyaldehydephenoxy)butane, MoO 2 Cl 2 (DMF) 2 and amino-modified magnetite nanoparticles (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[16,[19][20][21][22][23][24][25] Nowadays, magnetite nanoparticles are of particular interest because of their unique properties including high surface area, low toxicity, ability to be separated and biocompatibility. [16,[26][27][28][29][30] Magnetic separation renders the recycling of catalysts from solution using external magnetic fields much easier than filtration and centrifugation. In continuation of our previous investigation of catalytic activity of Schiff base complexes, [6,[9][10][11]15,19] herein we report the anchoring of novel cisdioxomolybdenum(VI) macrocyclic Schiff base complex by reaction of 1,4-bis(2-carboxyaldehydephenoxy)butane, MoO 2 Cl 2 (DMF) 2 and amino-modified magnetite nanoparticles (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the polarity, low coordinating ability and aprotic nature of acetonitrile are play the main role in improving the activity of the catalyst . Besides, it seems that polar solvents have a significant effect on the activation of intermediate species in manganese–porphyrin compounds and increase their catalytic activity . In fact, organic polar solvents, such as CH 3 CN, could affect access of substrate to active sites by increasing the solubility and diffusion of reactants in ILs …”
Section: Resultsmentioning
confidence: 99%
“…Oxygenation of the olefin seems to occur via a reactive high‐valent Mn–oxo intermediate, which is produced by the reaction of the peroxyacid with the Mn–porphyrin of p(APTMACl)‐[Mn(TPPS)(OAc)]. The high‐valent Mn–oxo intermediate then reacts with the olefin to generate the epoxide (as shown in Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…34 In the same year, Paul Le Maux et al reported an enantioselective water soluble iron porphyrin as catalyst for the asymmetric epoxidation of alkenes with iodobenzene diacetate as an oxidant. 38 In the same year, we reported asymmetric epoxidation of styrene and its derivatives, which were catalyzed by insitu metal complexes of chiral porphyrin ligands. 36 In the year 2015, Wen Dai et al reported porphyrin inspired iron catalyst for the asymmetric epoxidation of electron defecient olefins.…”
Section: Introductionmentioning
confidence: 99%